Perancangan Sistem e-Library Berbasis Web Jurusan Teknik Elektro Politeknik Negeri Padang - Nasrul - - (Jurnal Ilmiah Poli Rekayasa, 2017)
Data communication technology allows the building of a network of  computers with online applications.  With the Padang  State  Polytechnic  library  system  that  still  uses  a manual  system in the form of  books  and  cards – cards that contain data – data book is considered not efficient anymore, so it takes a library of WEB - based information systems. With the utilization of internet technology in tended for delivery and the need for rapid information retrieval, facilitate student and informed the user in the title of books desired, assist the Polytechnic library Country Meadow in logging the books, because of the internet as a very broad network is an effective and efficient means for this application.